UPAYA HUKUM TERHADAP ILLEGAL FISHING KAPAL PENANGKAP IKAN VIETNAM DI ZEEI - Amandha Budhy Adhywidya; Anto Ismu Budianto (Reformasi Hukum Trisakti, 2023)
Indonesia is a coastal nation with a 3,000,000 km2 EEZ that is rich in both biological and non-biological resources. Vietnamese fisherman are among those who engage in illegal fishing within the EEZ, or more specifically within the North Natuna Sea. How do fishing zones in Indonesia's Exclusive Economic Zone (EEZ) get regulated by the government, and what legal measures is the Indonesian government taking to deal with Vietnamese fishing vessels engaging in unlawful fishing in the North Natuna Sea? The research uses deductive in character, descriptive in nature, uses secondary data sources, qualitative data analysis, and is based on library research. The study's findings showed that starting in May 2021 to February 2022 as many as 75 Vietnamese fishing vessels carried out illegal fishing in the North Natuna Sea. The discussion in this study describes efforts to settle the EEZ boundary between Indonesia and Vietnam in the North Natuna Sea region based on Indonesian national law and UNCLOS. The conclusion in this study is that the Government of Indonesia is obliged to hasten the completion of the EEZ boundary between Indonesia and Vietnam based on the applicable provisions and equip the Indonesian navy with advanced technology and/or more adequate weapons.